On Greek religion - Parker, Robert, 1950- (Ithaca : Cornell University Press, 2011)
Robert Parker offers a provocative and wide-ranging entrance into the world of ancient Greek religion, focusing especially on the interpretive challenge of studying a religious system that in many ways remains desperately alien from the vantage point of the twenty-first century. --from publisher description.
Why believe without revelation? : the evidences of Greek religion -- Religion without a church : religious authority in Greece -- Analyzing Greek gods -- The power and nature of heroes -- Killing, dining, communicating -- The experience of festivals -- The varieties of Greek religious experience.
Includes bibliographical references and index.
Print version record.
Keywords: Greece -- Religion; HISTORY -- Ancient -- Greece; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Antiquities & Archaeology; Religion; Greece; Religion; Griechenland; Electronic books; Electronic book